UJI KEMURNIAN BENSIN DI SPBU DAN PENGECER SE-KOTA PADANG MENGGUNAKAN METODE SPEKTROSKOPI SERAPAN ATOM MERKURI - Shafii, Mohammad Ali; Harmadi, Harmadi; Ihksan, Khairatul; Herlina, Seni; Tongkukut, J. (Sainstek : Jurnal Sains dan Teknologi, 2010)
The gasoline purity test has been carried out in several retailers inPadangcity using Mercury atomic absorption spectroscopy method. As an object of study was taken 10 samples of gasoline were sold in stalls scattered retailers in the city ofPadang, for subsequent comparison with standard samples that taken from Pertamina Teluk Kabung Padang. Spectrum produced by each sample was analyzed based percentage difference between the spectrum peak, the angle position and the sample wavelength. To determine the level of gas purity, the mixing gasoline with kerosene have been done with the percentage ratio of 5% to 25%. From this research, it appears that gasoline retailers in the region of Batas Kota, Air Pacah and Pasar Baru indicating that the mixing of gasoline and kerosene to achieve the highest percentage, namely 25.3%, 23.2% and 17.2%. Meanwhile, the regions with the lowest percentage of blending gasoline and kerosene are in the area of Tunggul Hitam, Kuranji and Bungus, namely 3.7%, 5.0% and 4.9%.Key words: purity, gasoline, several retailers, atomic spectrum